MEDICAL AND PSYCHOLOGICAL REHABILITATION OF COMBATANTS AND ADAPTATION OF ITS MODEL TO MARTIAL LAW CONDITIONS - Aleschenko, Viktor (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article provides an analysis of the core components of the medical and psychological rehabilitation (MPR) model for combatants, including principles and objectives, the main phases of restoring the psychophysical resilience of service personnel exposed to combat stress under martial law. It examines practical experience gained during the implementation of MPR measures within the Defence Forces of Ukraine during the large-scale armed aggression by the Russian Federation. Current challenges in maintaining the mental health of combatants are highlighted. The paper explores the influence of combat environment factors on service personnel and the various types of psychological support provided to those suffering from symptoms of post-traumatic stress disorder (PTSD). It emphasises that timely and accurate identification of the type of acute combat stress reaction is a critical condition for mitigating its detrimental impact on the mental health of a soldier. M e t h o d s . The study applies both theoretical methods – content analysis, synthesis, generalization – and empirical methods such as observation and interviews. R e s u l t s . Firstly, it has been established that the legal framework of Ukraine only partially regulates the rehabilitation of combatants. The research identifies areas within the medical and psychological rehabilitation and readaptation system that require improvement in order to effectively address the adverse consequences of combat exposure among Defence Forces personnel and ensure successful transition to civilian life. Secondly, it defines the key components of the MPR model for combatants under martial law, which include: measures to prevent adverse mental health conditions among service members; the principles, objectives, and stages of rehabilitation; assessment of levels of sociopsychological maladaptation; development of a comprehensive set of recovery-stage rehabilitation actions; and social-psychological adaptation of combatants. Thirdly, the article underscores the necessity for coordinated efforts between the state and civil society, taking into account best practices in psychological support used by the armed forces of NATO partner states. It advocates for accelerating the development of a structured Psychological Rehabilitation Programme for personnel during combat capability restoration, as well as a comprehensive transition system from military service to civilian life. C o n c l u s i o n s . The study formulates theoretical conclusions and offers practical recommendations for improving the effectiveness of the psychological rehabilitation system for combatants under current conditions. It also proposes enhancements to the transition framework to ensure smoother reintegration of personnel into civilian life and stronger social protection.